Recycled ultra-high performance concrete based on full-scale utilization of waste concrete and preparation method of recycled ultra-high performance concrete

By using regenerated micro powder, fine aggregate and coarse aggregate to replace traditional materials in ultra-high performance concrete, and combining components such as silica fume and fly ash, we design regenerated ultra-high performance concrete with high mechanical properties, solving the cost of raw materials The problems of high and insufficient performance have achieved the goal of high intensity and low carbon green development.

CN119306440APending Publication Date: 2025-01-14SUZHOU CONCRETE CEMENT PROD RES INST +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411412603.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing ultra-high-performance concrete is relatively strict in raw material selection, which leads to expensive preparation costs and is accompanied by high energy consumption and high carbon emissions, which limits its further promotion and application. At the same time, the performance of recycled aggregates is insufficient, making it difficult to meet the requirements of ultra-high-performance concrete. .

Method used

Recycled fine powder, recycled fine aggregate and recycled coarse aggregate instead of machine sand, gravel and cement, combined with blends such as silica fume, fly ash, etc., to achieve the closest packing state through the design of specific dosages and components, and prepare Regenerated ultra-high performance concrete with high mechanical properties and optimized formulation with steel fibers and water reducers.

Benefits of technology

The compressive strength of recycled ultra-high performance concrete has reached more than 120MPa and tensile strength has reached more than 5MPa. At the same time, the production cost has been significantly reduced, and the resource utilization of solid waste and low-carbon green development have been achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306440A_ABST
    Figure CN119306440A_ABST
Patent Text Reader

Abstract

The invention relates to recycled ultra-high performance concrete based on full-scale utilization of waste concrete and a preparation method of the recycled ultra-high performance concrete. The raw materials comprise the following components: 380-430 parts of Portland cement; 120 to 170 parts of silica fume; 130 to 180 parts of fly ash; 50 to 100 parts of regenerated micro powder; 430 to 480 parts of machine-made sand; 430 to 480 parts of recycled fine aggregate; 270 to 320 parts of broken stone; 240 to 290 parts of recycled coarse aggregate; 150 to 170 parts of steel fiber; 50 to 60 parts of additional water; 120 to 140 parts of water for mixing; and 20-30 parts of a water reducing agent. The compressive strength of the regenerated ultra-high performance concrete can reach 120 MPa or above, the tensile strength can reach 5 MPa or above, the production cost of the regenerated ultra-high performance concrete is remarkably reduced, and resource utilization of solid waste can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of concrete, and in particular relates to a recycled ultra-high performance concrete based on full-scale utilization of waste concrete and a preparation method thereof. Background Art

[0002] Ultra-high performance concrete is the most innovative cement-based structural engineering material in recent years. It has the advantages of extremely high strength, good workability, excellent durability, etc. It has been widely used in many fields such as bridge engineering, tunnel engineering, high-rise buildings, maintenance and reinforcement. However, ultra-high performance concrete is relatively strict in the selection of raw materials. It must use high-quality raw materials (such as high-quality cement, silica fume, fly ash, quartz sand, etc.), which makes its preparation cost expensive and limits its further promotion and application. In addition, the production of high-quality raw materials will inevitably cause a large number of problems such as high energy consumption and high carbon emissions, which is not in line with the country's sustainable development strategy. Therefore, the development of new materials to replace the cementitious materials and fine aggregates of ultra-high performance concrete is of great significance to reducing the preparation cost of ultra-high performance concrete and achieving low-carbon and green development.

[0003] After the waste concrete is selected, crushed, and screened, recycled aggregates of various particle sizes are obtained. The particle size is no more than 4.75mm for recycled fine aggregate, and more than 4.75mm for recycled coarse aggregate. In the process of preparing recycled aggregate, some powder with a particle size less than 75μm is produced as recycled micro powder. The use of recycled fine aggregate, recycled coarse aggregate and recycled micro powder to replace machine-made sand, gravel and cement to prepare ultra-high performance concrete will surely bring significant economic and social benefits. However, the surface of the recycled aggregate has the disadvantages of residual old cement mortar, micro cracks in itself, and low strength, which leads to poor performance of the prepared concrete and makes it difficult to meet the performance requirements of ultra-high performance concrete. Summary of the invention

[0004] In view of the shortcomings of the prior art, one of the objects of the present invention is to provide an improved recycled ultra-high performance concrete based on the full-scale utilization of waste concrete. The compressive strength of the recycled ultra-high performance concrete can reach more than 120MPa, the tensile strength can reach more than 5MPa, and the production cost is significantly reduced, which can realize the resource utilization of solid waste.

[0005] Another object of the present invention is to provide a method for preparing recycled ultra-high performance concrete based on full-scale utilization of waste concrete. The preparation method has a simple process, low production cost, and can realize the resource utilization of solid waste.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A recycled ultra-high performance concrete, wherein the raw materials of the recycled ultra-high performance concrete include the following components in parts by weight: 380-430 parts of silicate cement; 120-170 parts of silica fume; 130-180 parts of fly ash; 50-100 parts of recycled micro powder; 430-480 parts of machine-made sand; 430-480 parts of recycled fine aggregate; 270-320 parts of crushed stone; 240-290 parts of recycled coarse aggregate; 150-170 parts of steel fiber; 50-60 parts of additional water; 120-140 parts of mixing water; and 20-30 parts of water reducer.

[0008] In the present invention, additional water refers to water used to pre-wet the recycled fine aggregate and recycled coarse aggregate to make them reach a saturated surface dry water absorption state. Mixing water refers to water used for concrete mixing and participating in the hydration reaction.

[0009] In some specific embodiments, the raw materials of the recycled ultra-high performance concrete include the following components, measured by weight: 400-415 parts of silicate cement; 130-160 parts of silica fume; 140-165 parts of fly ash; 60-90 parts of recycled micro powder; 440-480 parts of machine-made sand; 440-480 parts of recycled fine aggregate; 270-310 parts of crushed stone; 240-280 parts of recycled coarse aggregate; 150-160 parts of steel fiber; 50-60 parts of additional water; 120-140 parts of mixing water; and 25-30 parts of water reducer.

[0010] In some specific embodiments, the regenerated fine powder is a powder with a sieve size less than 75 μm during the preparation of the regenerated aggregate, and the activity index is ≥ 60%. In the present invention, the test method of the activity index is carried out in accordance with the provisions of JG / T 573.

[0011] In some specific embodiments, the particle size of the machine-made sand is 0.15-4.75 mm.

[0012] In some specific embodiments, the apparent density of the machine-made sand is 2600 kg / m 3 above.

[0013] In some specific embodiments, the MB value of the machine-made sand is less than 1.0. The MB value is an important indicator for measuring the quality of machine-made sand. It represents the methylene blue value and is used to evaluate whether the main component of fine powder in the machine-made sand is clay or stone powder. The MB value directly affects the performance of concrete, including workability, mechanical properties, early plastic cracking and shrinkage.

[0014] In some specific embodiments, the particle size of the recycled fine aggregate is 0.15-4.75 mm.

[0015] In some specific embodiments, the crushing index of the recycled fine aggregate is less than 20%. In the present invention, the test method of the crushing index is carried out in accordance with the provisions of GB / T 25176.

[0016] In some specific embodiments, the saturated surface dry water absorption of the recycled fine aggregate is less than 10%. In the present invention, the test method of saturated surface dry water absorption is carried out in accordance with the provisions of machine-made sand in GB / T 14684.

[0017] In some specific embodiments, the crushed stone has a particle size of 4.75-9.50 mm.

[0018] In some specific embodiments, the apparent density of the crushed stone is 2800 kg / m 3 above.

[0019] In some specific embodiments, the particle size of the recycled coarse aggregate is 4.75-9.50 mm.

[0020] In some specific embodiments, the crushing index of the recycled coarse aggregate is less than 20%.

[0021] In some specific embodiments, the saturated surface dry water absorption of the recycled coarse aggregate is less than 5%.

[0022] In some specific embodiments, the silicate cement is silicate cement having a strength of not less than 52.5 MPa.

[0023] In some specific embodiments, the silicate cement conforms to the silicate cement of GB175-2023 "General silicate cement" and has a strength grade of 52.5 or above.

[0024] In some specific embodiments, the average particle size of the silica fume is 0.1-1 μm.

[0025] In some specific embodiments, the silica fume conforms to the silica fume specified in GB27690-2023 "Silica fume for mortar and concrete".

[0026] In some specific embodiments, the SiO2 content of the silica fume is greater than 90%.

[0027] In some specific embodiments, the fly ash is fly ash that complies with GBT1596-2017 "Fly ash used in cement and concrete".

[0028] In some specific embodiments, the steel fiber is a hook-end copper-plated steel fiber.

[0029] In some specific embodiments, the length of the steel fiber is 10-20 mm and the diameter is 0.10-0.30 mm. Preferably, the length of the steel fiber is 14 mm and the diameter is 0.22 mm.

[0030] In some specific embodiments, the tensile strength of the steel fiber is above 2000 MPa.

[0031] In some specific embodiments, the water reducer is a polycarboxylate water reducer.

[0032] In some specific embodiments, the water reducing agent has a water reducing rate of 30% or more.

[0033] The present invention also provides a method for preparing the aforementioned recycled ultra-high performance concrete, the preparation method comprising the following steps: mixing the machine-made sand, recycled fine aggregate, crushed stone, recycled coarse aggregate and additional water to obtain wet aggregate; mixing the silicate cement, silica fume, fly ash, recycled micro powder and the wet aggregate to obtain a mixture; adding the mixing water and water reducer to the mixture for mixing; then adding steel fiber to mix, casting and curing to obtain the recycled ultra-high performance concrete.

[0034] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0035] The present invention adopts recycled micro powder to replace part of cement, compounds recycled fine aggregate with machine-made sand, compounds recycled coarse aggregate with crushed stone, and controls the contents of recycled micro powder, recycled fine aggregate, machine-made sand, recycled coarse aggregate and crushed stone. Since the particle size of the recycled fine aggregate is equivalent to that of the machine-made sand, and the particle size of the recycled coarse aggregate is equivalent to that of the crushed stone, by adopting the specific dosage of various components of the present invention, the various components can be achieved in the most densely stacked state, thereby making the mechanical properties of the recycled ultra-high performance concrete higher, the compressive strength can reach more than 120MPa, the tensile strength can reach more than 5MPa, and the production cost is significantly reduced, and the resource utilization of solid waste can be realized.

[0036] The present invention is based on the closest packing theory, adopts a compound of recycled fine aggregate and machine-made sand, a compound of recycled coarse aggregate and crushed stone, and controls the dosage of the four, and simultaneously adds admixtures such as silica fume and fly ash to exert the volcanic ash effect and filling effect, improve the state of concrete, and prepare ultra-high performance concrete with good performance, which solves the problem of the increasing shortage of natural sand and stone resources, reduces production costs, and is conducive to sustainable development.

[0037] The present invention adopts recycled micropowder to replace cement. The mineral composition of the recycled micropowder mainly includes SiO2, CaCO3, hydrated calcium silicate and a small amount of ettringite, etc. It has certain activity and participates in the hydration of cement together with mineral admixtures to generate partial hydration products to fill pores, enhance the density of concrete, promote the utilization of solid waste, and achieve green and low-carbon.

[0038] The ultra-high performance concrete made of machine-made sand prepared by the synergistic use of multiple solid wastes in the present invention has a compressive strength of more than 120 MPa and a tensile strength of more than 5 MPa after 28 days of standard curing. On the basis of ensuring the basic mechanical properties of ultra-high performance concrete, it realizes the common resource utilization of multiple solid wastes such as recycled micropowder, recycled fine aggregate and recycled coarse aggregate. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The particle size distribution and close packing curve of each raw material in Example 1. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention, but the present invention is not limited to the scope of the examples.

[0041] Unless otherwise specified, the raw materials used in this application can be obtained from commercial sources.

[0042] In the following examples and comparative examples:

[0043] Cement, strength grade 52.5, 28d compressive strength 57.0MPa;

[0044] Silica fume, grade SF90, SiO2 content 95%, activity index 120%;

[0045] Fly ash, grade Ⅰ, activity index 80%;

[0046] Regenerated micro powder, particle size is less than 0.75mm, activity index is 65%, the main chemical composition is shown in Table 1 (it also contains a small amount of other components, which are not listed);

[0047] Table 1

[0048] Element <![CDATA[SiO2]]> CaO <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> MgO content / % 44.25 29.88 14.00 4.06 2.72

[0049] Machine-made sand, particle size range 0.15-4.75mm, apparent density 2660kg / m 3 , MB value 0.95;

[0050] Recycled fine aggregate, particle size range 0.15-4.75mm, apparent density 2450kg / m 3, crushing index 20%, saturated surface dry water absorption 9%;

[0051] Crushed stone, particle size range 4.75-9.50mm, apparent density 2900kg / m 3 ;

[0052] Recycled coarse aggregate, particle size range 4.75-9.50mm, apparent density 2600kg / m 3 , crushing index 15%, saturated surface dry water absorption 4.9%;

[0053] Steel fiber, length 14mm, diameter 0.22mm, tensile strength 2000MPa;

[0054] Water reducing agent, solid content 27%, water reduction rate 30%.

[0055] Example 1

[0056] This embodiment provides a recycled ultra-high performance concrete, and its raw material formula (by weight) is shown in Table 2.

[0057] The particle size distribution and close packing curves of each raw material (target curve, actual curve of Example 1) are as follows: Figure 1 As shown, it can be seen that the stacking method of Example 1 is basically close to the target dense stacking method.

[0058] Prepared by the following method:

[0059] Weigh each raw material according to the weight portion in Table 2; pour the weighed machine-made sand, recycled fine aggregate, crushed stone and recycled coarse aggregate into a forced horizontal shaft mixer, add additional water and stir for 1 minute to fully wet the aggregate; then add the weighed cement, silica fume, fly ash and recycled micro powder, stir with the aggregate for 1 minute to mix them evenly; then add the weighed mixing water and water reducing agent, stir for 4 minutes, add the weighed steel fiber after the concrete is fully fluidized, continue stirring for 2 minutes, and after casting and curing, obtain the recycled ultra-high performance concrete based on the full-scale utilization of waste concrete.

[0060] Example 2-3

[0061] This embodiment provides a recycled ultra-high performance concrete, which is basically the same as Embodiment 1, except that the raw material formula is different, see Table 2 for details.

[0062] Comparative Example 1

[0063] This comparative example provides a recycled concrete, which is basically the same as Example 1, except that the raw material formula is different, the recycled micro powder content is increased, and the cement content is correspondingly reduced, see Table 2 for details.

[0064] Comparative Example 2

[0065] This comparative example provides a recycled concrete, which is basically the same as Example 1, except that the raw material formula is different, the amount of recycled fine aggregate is increased, and the amount of machine-made sand is correspondingly reduced, see Table 2 for details.

[0066] Comparative Example 3

[0067] This comparative example provides a recycled concrete, which is basically the same as Example 1, except that the raw material formula is different, the amount of recycled coarse aggregate is increased, and the amount of crushed stone is correspondingly reduced, see Table 2 for details.

[0068] Comparative Example 4

[0069] This comparative example provides a recycled concrete, which is basically the same as Example 1, except that the raw material formula is different and the amount of cementitious material is reduced. See Table 2 for details.

[0070] Comparative Example 5

[0071] This comparative example provides a recycled concrete, which is basically the same as Example 1, except that the raw material formula is different and the amount of cementitious material is increased, see Table 2 for details.

[0072] The amount of additional water in Table 2 is calculated using the method in the specification.

[0073] Table 2 Raw material formula of each embodiment and comparative example (by weight)

[0074]

[0075]

[0076] Performance testing

[0077] According to the standard T / CBMF37-2018 T / CCPA7-2018 "Basic Properties and Test Methods of Ultra-High Performance Concrete", the compressive strength and tensile strength of the concrete of the above embodiments and comparative examples were measured. The compressive strength test block was a 100×100×100 mm cubic test block, and the tensile strength test block was a dumbbell-shaped test block with a length of 368 mm, a width of 100 mm, and a thickness of 50 mm. The measurement results are shown in Table 3.

[0078] Table 3 Compressive strength and flexural strength of each embodiment and comparative example

[0079] Group Compressive strength / MPa Tensile strength / MPa Example 1 125.9 6.1 Example 2 123.8 5.4 Example 3 125.3 5.6 Comparative Example 1 117.5 4.9 Comparative Example 2 115.3 4.8 Comparative Example 3 120.2 5.1 Comparative Example 4 107.6 3.8 Comparative Example 5 114.4 4.2

[0080] As can be seen from Table 3, after 28 days of standard curing, the regenerated ultra-high performance concrete based on the full-scale utilization of waste concrete prepared by the present invention has a compressive strength of more than 120 MPa and a tensile strength of more than 5 MPa. Therefore, the mechanical properties of the regenerated ultra-high performance concrete based on the full-scale utilization of waste concrete prepared by the present invention meet the engineering application requirements of ultra-high performance concrete. In addition, it can be seen from the strength test results of Comparative Examples 1 to 5 that the strength of concrete materials with excessive addition of recycled micropowder, recycled fine aggregate, recycled coarse aggregate, and too low or too high a cementitious material dosage is significantly reduced, and can no longer meet the mechanical property requirements of ultra-high performance concrete.

[0081] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0082] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A recycled ultra-high performance concrete, characterized in that: The raw materials of the recycled ultra-high performance concrete include the following components by weight: 380-430 parts of silicate cement; 120-170 parts of silica fume; 130-180 parts of fly ash; 50-100 parts of recycled micro powder; 430-480 parts of machine-made sand; 430-480 parts of recycled fine aggregate; 270-320 parts of crushed stone; 240-290 parts of recycled coarse aggregate; 150-170 parts of steel fiber; 50-60 parts of additional water; 120-140 parts of mixing water; 20-30 parts of water reducer.

2. The recycled ultra-high performance concrete according to claim 1, characterized in that: The raw materials of the recycled ultra-high performance concrete include the following components by weight: 400-415 parts of silicate cement; 130-160 parts of silica fume; 140-165 parts of fly ash; 60-90 parts of recycled micro powder; 440-480 parts of machine-made sand; 440-480 parts of recycled fine aggregate; 270-310 parts of crushed stone; 240-280 parts of recycled coarse aggregate; 150-160 parts of steel fiber; 50-60 parts of additional water; 120-140 parts of mixing water; 25-30 parts of water reducer.

3. The recycled ultra-high performance concrete according to claim 1, characterized in that: The regenerated fine powder is powder with a sieving size of less than 75 μm during the preparation of the regenerated aggregate, and the activity index is ≥60%.

4. The recycled ultra-high performance concrete according to claim 1, characterized in that: The particle size of the machine-made sand is 0.15-4.75 mm; and / or the apparent density of the machine-made sand is 2600 kg / m 3 and / or, the methylene blue value MB of the machine-made sand is below 1.

0.

5. The recycled ultra-high performance concrete according to claim 1, characterized in that: The particle size of the recycled fine aggregate is 0.15-4.75 mm; and / or the crushing index of the recycled fine aggregate is less than 20%; and / or the saturated surface dry water absorption rate of the recycled fine aggregate is less than 10%.

6. The recycled ultra-high performance concrete according to claim 1, characterized in that: The particle size of the crushed stone is 4.75-9.50 mm; and / or the apparent density of the crushed stone is 2800 kg / m 3 above.

7. The recycled ultra-high performance concrete according to claim 1, characterized in that: The particle size of the recycled coarse aggregate is 4.75-9.50 mm; and / or the crushing index of the recycled coarse aggregate is less than 20%; and / or the saturated surface dry water absorption rate of the recycled coarse aggregate is less than 5%.

8. The recycled ultra-high performance concrete according to claim 1, characterized in that: The silicate cement is a silicate cement having a strength of not less than 52.5 MPa; and / or the average particle size of the silica fume is 0.1-1 μm; and / or the SiO2 content of the silica fume is above 90%; and / or the fly ash is fly ash that complies with GBT1596-2017 "Fly ash used in cement and concrete".

9. The recycled ultra-high performance concrete according to claim 1, characterized in that: The steel fiber is a hook-end copper-plated steel fiber; and / or the length of the steel fiber is 10-20 mm and the diameter is 0.10-0.30 mm; and / or the tensile strength of the steel fiber is above 2000 MPa; and / or the water reducer is a polycarboxylic acid water reducer; and / or the water reduction rate of the water reducer is above 30%.

10. A method for preparing recycled ultra-high performance concrete according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: mixing the machine-made sand, recycled fine aggregate, crushed stone, recycled coarse aggregate and additional water to obtain wet aggregate; mixing the silicate cement, silica fume, fly ash, recycled micro powder and the wet aggregate to obtain a mixture; adding the mixing water and water reducing agent to the mixture for mixing; then adding steel fiber to mix, casting and curing to obtain the recycled ultra-high performance concrete.

Citation Information

Cited By

  • Preparation method of high-impermeability fiber-reinforced recycled aggregate concrete and product

    CN119977430A

  • Preparation method and product of fiber-reinforced recycled aggregate concrete with high impermeability

    CN119977430B